CURRENT ISSUES IN THE TRAINING OF PHYSICAL EDUCATION SPECIALISTS (International journal of artificial intelligence, 2025)
This article examines the formation of thinking style and cognitive approaches among future specialists in physical education and sports within the context of modern social, cultural, and athletic practices. It is scientifically substantiated that globalization, the rapid increase in information flows, growing competition in the sports sphere, and the rising demands of contemporary education systems necessitate the renewal and development of thinking styles. The article provides an extensive analysis of the worldview, motivation, psychological processes in sports activities, and the interrelation of tactical and creative thinking among future professionals.